The Covid pandemic in the market: Infected, immune and cured bonds - Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
By focusing on the cost conditions at issuance, I find that not only the Covid-19 pandemic effects were different across bonds and firms at different stages, but also that the market composition was significantly affected, collapsing on investment- grade bonds, a segment in which the share of bonds eligible to the ECB corporate programmes strikingly increased from 15% to 40%. At the same time the high-yield segment shrunk to almost disappear at 4%. In addition to a market segmentation along the bond grade and the eligibility to the ECB programmes, another source of risk detected in the pricing mechanism is the weak resilience to pandemic: the premium requested is around 30 basis points and started to be priced only after the early containment actions taken by the national authorities. On the contrary, I do not find evidence supporting an increased risk for corporations headquartered in countries with a reduced fiscal space, nor the existence of a premium in favour of green bonds, which should be the backbone of a possible "green recovery".
urn:nbn:de:hebis:30:3-575781
Keywords: G15; G32; E52; 330; ECB; Corporate quantitative easing; Covid pandemic; Green bonds